Determination of Lipoxygenase, CYP450, and Non-Enzymatic Metabolites of Arachidonic Acid in Essential Hypertension and Type 2 Diabetes - Guillaume Feugray; Tony Pereira; Michèle Iacob; Lucile Moreau-Grangé; Gaëtan Prévost; Valéry Brunel; Robinson Joannidès; Jérémy Bellien; Thomas Duflot (Metabolites, 2022)
Type 2 diabetes (T2D) and hypertension (HTN) are common risk factors of cardiovascular diseases (CVD) characterized by chronic low-grade systemic inflammation and impaired endothelial function. This study aimed to assess whether levels of non-enzymatic, lipoxygenase (LOX)- and cytochrome P450 (CYP)-derived arachidonic acid (ARA) metabolites, which are known regulators of vascular homeostasis, are affected by HTN and T2D. For this objective, 17 plasma level derivatives of ARA were quantitated by chromatography coupled with mass spectrometry in 44 patients (12 healthy, 8 HTN, 7 T2D, and 17 HTN + T2D). Effects of hyperglycemic and hyperinsulinemic clamps on ARA metabolite levels were assessed in seven healthy subjects. No significant differences in the plasma levels of ARA metabolites were observed for T2D patients compared with healthy volunteers. HTN was associated with an alteration of ARA metabolite correlation patterns with increased 20-, 19-, 15-, and 8-hydroxyeicosatrienoic acid (HETE). A decrease of 20-HETE was also observed during both hyperglycemic and hyperinsulinemic clamps. Additional experiments are needed to assess whether the modulation of HETE metabolites in HTN may be of interest. Furthermore, although not affected by T2D, it remains to investigate whether the decrease of 20-HETE observed during clamps may be related to the regulation of glucose tolerance and insulin signaling.